2021
DOI: 10.3389/fonc.2021.577514
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection and Lung Cancer Immunotherapy

Abstract: Immunotherapy with immune checkpoint inhibitors (mainly anti-PD1 and anti-PDL1 monoclonal antibodies) became a standard of care in non-small cell lung cancer (NSCLC) patients. Most of the clinical trials excluded patients with hepatitis B (HBV), hepatis C (HCV), and human immunodeficiency virus (HIV) active infection (1–10). Despite the progress in treatment of these infections, they remain an unresolved clinical problem when lung cancer immunotherapy should be initiated in an NSCLC patient. This manuscript su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Inflammation is also an important part of the tumor environment and plays an important role in the development and progression of malignant tumors [53] . Cancer patients, as one of the most susceptible populations, are facing severe disadvantages during the COVID-19 epidemic, lung cancer patients, in particular [54] , have been reported to be more susceptible to SARS-Cov-2 infection and they are at higher risk of developing pneumonia and severe complications of COVID-19 on admission [55] . ACE2 is a functional receptor for SARS-CoV-2 to enter and replicate in host cells [56] , and its expression level is thought to indicate susceptibility to COVID-19 [57] , the expression level of ACE2 in lung tissue is increased [58,59] and according to the analysis of a study, it is found that the messenger RNA (mRNA) expression of ACE2 is higher in lung and colorectal cancer than other types of cancer [60] , which may be another explanation for lung cancer patients being more susceptible to SARS-CoV-2 infection and at higher risk of severe COVID-19.…”
Section: Table 4: Molecular Docking Of Colchicine With Core Target Pr...mentioning
confidence: 99%
“…Inflammation is also an important part of the tumor environment and plays an important role in the development and progression of malignant tumors [53] . Cancer patients, as one of the most susceptible populations, are facing severe disadvantages during the COVID-19 epidemic, lung cancer patients, in particular [54] , have been reported to be more susceptible to SARS-Cov-2 infection and they are at higher risk of developing pneumonia and severe complications of COVID-19 on admission [55] . ACE2 is a functional receptor for SARS-CoV-2 to enter and replicate in host cells [56] , and its expression level is thought to indicate susceptibility to COVID-19 [57] , the expression level of ACE2 in lung tissue is increased [58,59] and according to the analysis of a study, it is found that the messenger RNA (mRNA) expression of ACE2 is higher in lung and colorectal cancer than other types of cancer [60] , which may be another explanation for lung cancer patients being more susceptible to SARS-CoV-2 infection and at higher risk of severe COVID-19.…”
Section: Table 4: Molecular Docking Of Colchicine With Core Target Pr...mentioning
confidence: 99%